THE EFFECTIVENESS OF AI-BASED LEARNING AND GAMIFICATION IN ENHANCING ACADEMIC ACHIEVEMENT: A LITERATURE REVIEW - Anis Yuliani; Arini Dwi Cahyani; Muh. Sholeh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This systematic literature review synthesizes empirical evidence on the effectiveness of AI-based learning and gamification—both independently and in combination—in improving students' academic achievement. Drawing from 124 peer-reviewed journal articles published between 2021 and 2026 extracted from Scopus, Web of Science, and ERIC databases, the analysis focuses on experimental, quasi-experimental, and meta-analytic studies across primary, secondary, and higher education contexts. Findings reveal that gamification consistently yields moderate-to-large positive effects on achievement (Hedge's g = 0.79–1.12), while AI-driven adaptive systems enhance outcomes through personalization (effect sizes 0.40–0.97). Combined AI-gamification approaches demonstrate the strongest gains by integrating real-time feedback, adaptive difficulty, and motivational game elements (g up to 1.24). Mechanisms include increased engagement, intrinsic motivation, and self-regulated learning. Challenges such as digital equity and over-reliance on extrinsic rewards are noted. The review concludes that integrating AI and gamification offers a scalable, evidence-based pathway to elevate academic achievement, with clear implications for curriculum design and teacher training.